Kualitas Pelayanan Izin Mendirikan Bangunan Pada Desa Waiheru Kota Ambon - Papalia, Erna; Wance, Marno; Rolobessy, Mike Jurnida (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2024)
The aim of this research is to find out how the quality of the service of the Building Permit Entry Letter (IMB) at the office of Waiheru Village, Baguala district, Ambon City. The research method used is descriptive research with a qualitative approach. The findings of this research are that the quality of the service of the building permit registration to the community that carries out the management of the Building License Registration in the Waiheru village office of Baguala district of Ambon has been running effectively, besides it is still a lack of public participation in building permit management (IMB) every year it rises down. And there's still a lot of people who haven't understood and are doing the management of letters of invitation to make building permits.